The effect of a permanent dipole moment on the polar molecule cavity quantum electrodynamics - 赵晶云 秦立国 蔡勋明 林强 王中阳 (Chinese physics B, 2016)
A dressed-state perturbation theory beyond the rotating wave approximation （RWA） is presented to investigate the interaction between a two-level electronic transition of polar molecules and a quantized cavity field. Analytical expressions can be explicitly derived for both the ground- and excited-state-energy spectrums and wave functions of the system, where the contribution of permanent dipole moments （PDM） and the counter-rotating wave term （CRT） can be shown separately. The validity of these explicit results is discussed by comparison with the direct numerical simulation. Compared to the CRT coupling, PDM results in the coupling of more dressed states and the energy shift is proportional to the square of the normalized permanent dipole difference, and a greater Bloch-Siegert shift can be produced in the giant dipole molecule cavity QED. In addition, our method can also be extended to the solution of the two-level atom Rabi model Hamiltonian beyond the RWA.